2001
DOI: 10.1002/1097-0142(20010801)92:3<556::aid-cncr1355>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor family members in head and neck squamous cell carcinoma correlates with lymph node metastasis

Abstract: BACKGROUND The expression of vascular endothelial growth factor (VEGF)‐A isoforms (121, 165, 189, 206), VEGF‐B, VEGF‐C and VEGF‐D in both experimental and clinical models of head and neck squamous cell carcinoma (HNSCC) was determined and correlated with conventional clinicopathologic parameters, with particular reference to cervical nodal metastasis. METHODS The mRNA expression of VEGFs in 14 HNSCC cell lines was compared with 4 normal keratinocyte cultures and 10 fibroblast cultures using a semiquantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
1
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(133 citation statements)
references
References 39 publications
8
112
1
12
Order By: Relevance
“…The current study also found that such tumours behaved more aggressively, as they were significantly associated with the presence of LN metastasis (Po0.001), distant metastasis (P ¼ 0.01) and a poorer survival (P ¼ 0.029). These findings are similar to others, both in breast cancer and other tumour types (Toi et al, 1995b;Linderholm et al, 1999;O-Charoenrat et al, 2001). Although the effect of VEGF-A expression can be mediated by an increased vascular network, it should be noted that the growth factor has also been shown to increase breast cancer cell survival through direct action on VEGFR-2 that has been found to be expressed on the surface of the breast cancer cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study also found that such tumours behaved more aggressively, as they were significantly associated with the presence of LN metastasis (Po0.001), distant metastasis (P ¼ 0.01) and a poorer survival (P ¼ 0.029). These findings are similar to others, both in breast cancer and other tumour types (Toi et al, 1995b;Linderholm et al, 1999;O-Charoenrat et al, 2001). Although the effect of VEGF-A expression can be mediated by an increased vascular network, it should be noted that the growth factor has also been shown to increase breast cancer cell survival through direct action on VEGFR-2 that has been found to be expressed on the surface of the breast cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported to be significantly associated with high LVD, LN metastasis and poorer survival in gastric (Shida et al, 2005), endometrial (Yokoyama et al, 2003) and colorectal carcinomas (White et al, 2002). In head and neck tumours (O-Charoenrat et al, 2001), such relationships have not been found. In other studies in breast and in lung carcinoma, low levels of expression of VEGF-D was associated with poorer prognosis (Niki et al, 2000;Koyama et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…In light of the present results, it will also be important for the future analysis of VEGF-D expression in tumors to take into account that VEGF-D might be expressed as a late marker of tumor progression and only in cells that have lost or reduced expression of ␤-catenin. These analyses will probably clarify the apparent discrepancy of VEGF-D expression in tumors reported by different authors (31)(32)(33)(34)(35)(36)(37).…”
Section: The Presence Of Cellular Free ␤-Catenin Correlates With Vegfmentioning
confidence: 86%
“…Because constitutive ␤-catenin signaling has been correlated with colorectal cancer formation (57), its regulation of VEGF-D mRNA is particularly important considering that the expression of this factor has been correlated with tumor progression (33,34,36,37,58). In this respect, it is worth noting that ␤-catenin has been described as a master gene for cell proliferation (55), but its role in tumor progression is less clear.…”
Section: The Presence Of Cellular Free ␤-Catenin Correlates With Vegfmentioning
confidence: 99%
“…In line with their proposed role in cancer pathobiology, the expression of VEGF-C, VEGF-D, and/or VEGFR-3 has been shown to correlate with lymphatic spread, tissue invasion, and/or poor prognosis in solid malignancies (3) including gastric cancer (4). In other studies, however, conflicting observations were made (5,6) indicating that the role of the VEGF-C/VEGF-D/VEGFR-3 system in cancer is complex and may differ between malignancies.…”
Section: Introductionmentioning
confidence: 92%